Finite Element Analysis of Prestressed Concrete Sleeper Subject to Static Loading - Ikmal Fazlan Rozli, Mohd; Nadeera Kipperawi, Nur; Mohd Hilmi Safiuddin Che Jamaludin Mahmud, Che; Dora Abdul Ghani, Kay; Mohd Amin, Norliyati (International Journal of Engineering and Technology, 2018)
Railway is one of the most important, reliable, and widely used means of transportation, carrying freights, and passengers. Thus, a study on railway is indeed important for the development of railway engineering and technologies. Prestressed concrete sleepers are the main structural elements of railway tracks. They play a vital role in railway track performance, behaviour, and safety. The main objective of the study is to develop a three-dimensional finite element model of prestressed concrete sleeper to compare load-deflection of finite element analysis and experimental result and identify the behaviour of the sleeper subject to static loading. The three-dimensional element analysis is executed using LUSAS. A concrete element is modelled as a hexahedral element and prestressing tendon is modelled as a bar element. Later, a positive moment test is carried out on the model and at last, a validation of the finite element model through comparison with the experimental load-deflection response is presented in this study. Thus, good agreements between finite element analysis and experimental results make the work beneficial and reliable.Â Â